Hate Speech di Media Baru: Afeksi dan Etika Narasi dalam Komunikasi Publik - Hasan Sazali; Hendra Cipta (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2026)
This study examines how digital affect shapes the escalation of religion-based hate speech in the new media public sphere and disrupts Islamic communication ethics. Through one month of discourse observation on the X platform using Brand24, posts containing the keywords “goblok,” “tolol,” “kafir,” “hate speech,” and “ujaran kebencian” related to Islamic contexts were collected. The data were treated as discourse units to map patterns of wording, reach, and emotional tone, then interpreted using the normative framework of Islamic Communication Ethics and affect theory. The findings indicate a dominance of disgust and anger, the prevalence of derogatory labeling based on religious and intellectual identity, strong political-religious polarization, and the normalization of verbal aggression by influential accounts and media outlets. Negative affect emerges as a commodity that amplifies virality, while simultaneously driving dehumanization, the erosion of scholarly authority, and the weakening of hikmah, adab, and tabayun in public communication. The integration of Islamic moral philosophy with affect theory generates an ethical framework that reaffirms the necessity of hikmah, hilm, sidq, adab, and amanah as spiritual filters against the algorithmic structure of new media, ensuring that Islamic public communication returns to an orientation of enlightenment rather than emotional performativity.